Social Responsibility for Health during COVID-19 Pandemic - Shakya, Dhana Ratna; Shrestha, Ravi Ram; Koirala, Sarun; Kafle, Santosh Upadhyaya; Subedi, Prasanna; Anand, Ayush; Ghimire, Aparna; Gurung, Kishor; Pokharel, Krishna (Journal of BP Koirala Institute of Health Sciences, 2021)
Health is a fundamental right for which concerned sides should bear the responsibility at the individual, societal, state, and international level. Not only curative but preventive, promotive, and rehabilitative services should also be availed in accessible, affordable, and acceptable form. The quest for health becomes more intense during adverse periods like a pandemic. The whole world has witnessed the COVID-19 pandemic, the unprecedented pandemic of this century. This quest is more dismal in developing nations like Nepal when even resource- rich countries are laid down by it. The quest of health demands, hence more during this pandemic, for the bearing of the responsibility by all. Here, we have made an attempt to draw together the general and some specific responsibilities of various direct stakeholders in this pandemic with multifaceted mayhem. We have incorporated here, the responsibilities of the public, COVID and non-COVID patients, media personnel, health science students, professionals, institutions, state, and media to ensure or safeguard the health of self and others in this pandemic.